Klasztor w Kraśniku w przekazie Jana Długosza - Graff, Tomasz (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The author analyzes the information about Kraśnik and the monastery in Kraśnik included in Długosz's works, with particular emphasis on Liber Beneficiorum. Długosz's source is certainly a valuable supplement to other manuscripts related to the original endowment of the monastery of the Canons Regular of Lateran, who came to Kraśnik from Kazimierz (near Cracow), from the Corpus Christi Monastery. Długosz, however, made smaller and larger mistakes, so his source should be carefully verified. The author also gives a Polish translation of the most important fragments of Liber Beneficiorum about the Kraśnik monastery. The Kraśnik monastery played an important part in Polish culture, not only because of its book collection but also because of the special significance of the Polish language in this monastery. In the document issued by the bishop of Cracow, Jan Lutek from Brzezie, who approved the document of the founder, Jan Rabsztyński, on 13 March 1469, there is, among others, a regulation stating that a provost should be elected from those monks who could speak Polish fluently..